Diagnostic peritoneal lavage analysis: should trauma guidelines be revised?. Issue 6 (1st November 2002) - Maxwell-Armstrong, C; Brooks, A; Field, M; Hammond, J; Abercrombie, J
Abstract : Objectives: Diagnostic peritoneal lavage (DPL) is used to detect intraperitoneal bleeding in patients sustaining blunt and penetrating abdominal trauma. The procedure should be performed by an experienced general surgeon, and the fluid obtained analysed by haematology technicians. Current Advanced Trauma Life Support guidelines are very clear on what constitutes a positive result, mandating laparotomy. The aim of this work was to assess whether DPL could actually be performed in practice. Methods: A telephone survey was performed of a random selection of haematology technicians in 40 major trauma units in the UK, to assess whether they could actually analyse a DPL sample if it were sent to them. This was performed both during the day, and "out of hours". Secondly the experience of performing DPL was determined among 1797 general surgical trainees and consultants, by means of a questionnaire. Results: Between 9 am and 5 pm 29 of 40 haematology technicians questioned were able to analyse a sample of DPL fluid. This compared with a figure of 9 of 40 when the questionnaire was administered "out of hours". A total of 854 (48%) questionnaires were received from surgical trainees and consultants. Approximately 60% of those questioned had performed less than 10 DPLs throughout the whole of their careers. Discussion: These results suggest that UK surgeons have little experience in performing DPL, and even if they do it is unlikely that any haematology departments will be able to analyse the sample, especially if performed after 5 pm. ATLS guidelines should be changed, and this investigation abandoned in favour of abdominal ultrasound.